PERAN POLITIK DALAM KOMUNIKASI GERAKAN SOSIAL KOMUNITAS PERUBAHAN IKLIM - Firliandoko, Robby; Sarwoprasodjo, Sarwititi; Saleh, Amiruddin (Master of Communication Science Program, Universitas Diponegoro, 2023)
The Climate Smart Generation Community (GCI) is an example of a group of agents of change in the field of climate change who carry out social movement activities in the community to invite them to adapt, mitigate and save the environment. The Climate Smart Generation Community be an object of this research because it is a community that operates in the field of climate change through preventive and curative education for children to increase understanding of disaster mitigation and build the character of loving the environment from an early age. In social movements, politics is one of the supporting factors for inhibitors. This research using qualitative methods and constant comparative data analysis. Distance research data collection techniques support data collection through semi-structured interviews. The data collected is in the form of answers submitted by informants. The collected research data is then grouped, categorized, and themed into key terms, terms of equal value. These key terms are then connected, analyzed, and combined with existing research results as a form of support or refutation. This research found that political constellations at the regional to national levels did not significantly influence the movements carried out by GCI. In contrast to these conditions, local-level political stakeholders such as the RT to the Village Government provide support from permits to facilities in activities. Gatherings and proposals are the medium of communication used to gain local government support. Messages are one of the weapons for GCI to seek and gain support from political entities. The message regarding requests for sources and delivery of work programs to political entities, especially the government, was succesed. Not only getting support from seeds from the government, but GCI also gets support for access to other agencies and funding support through the competition process. Winning the race also resulted in trust from political entities.